Efektifitas Propolis Toothpaste sebagai Initial Therapy pada Mild Gingivitis - Nila Kasuma (Jurnal Sains Farmasi & Klinis, 2014)
Characteristics of mild gingivitis are change in the color of the gums, slight edema, and no bleeding and painless. If it does not receive the proper treatment, gingivitis can become periodontitis which cause alveolar jaw bone tissue damage, resulting in further tissue damage locally and systemically through the blood vessels. The selection of appropriate therapy is essential to reduce the prevalence of the disease. In addition to scaling and plaque control, the propolis toothpaste can be used as initial therapy. The toothpaste contains propolis known for anti-inflammatory effects that is useful as one of the initial teraphy to treat mild gingivitis. Gingival index of 15 patients were measured before and after use of propolis toothpaste. Data analysis was performed by means of univariate to describe each variabel using Kolmogorov Smirnof Test. Gingival Index difference between before and after brushing with toothpaste containing propolis by paired t-test. Toothpaste contains propolis which proved effective in the initial therapy of mild gingivitis with an average difference of reduction in Gingival Index scores before and after was 0.40 ± 0.04 There are significant differences (p <0.05) difference between the average reduction in Gingival Index scores before and after the use of toothpaste containing propolis.